Grandes estancias en la provincia de Buenos Aires, Argentina : Formación y consolidación del patrimonio rural en los partidos de Chascomús, Ranchos y Monte, 1780-1880 - Banzato, Guillermo (2002)
In this work we will study the formation, consolidation and business management of some large rural properties that originated in Chascomús, Monte and Ranchos, from its beginning as military forts in 1780 to the so-called "conquest to the desert" in 1879. For this we will confront measurements, records of land applications, cadastral registers, successions and wills, in order to determine the occupation and access to legal property and analyze the conditions of production, forms of exploitation and strategies of conservation of the heritage of large ranchers. Our study will include, first and foremost, those families that comprised the cohort of first settlers and that remained until 1880, without forgetting -especially to compare their strategies- with other families that arrived in the following decades and also lasted until the end of the period, the time we will appreciate the nuances in the development of the estancieros of these three parties.